Evaluation of rapid scanning techniques for inspecting concrete bridge decks with asphalt overlay - Vemuri, Sri Harsha, author; Atadero, Rebecca, advisor; Chen, Suren, committee member; Strong, Kelly, committee member (Colorado State University. Libraries, 2016)
The average age of bridges in the USA is 42 years. The life expectancy of a majority of these bridges is 50 years. At the current rates of aging and replacement, almost half of the nation’s bridges will require major structural investment in the next 15 years as stated by the Federal Highway Administration. There is a severe deficiency in both time and resources available to address this problem, and methods to increase efficiency are needed. Bridge decks are the most critical elements of a bridge structure as they are directly and continuously exposed to harsh weather conditions and cyclic loading from traffic throughout their lifespan. This thesis attempts to improve management practices for bridge decks by addressing current challenges faced by the Colorado Department of Transportation (CDOT) in estimating the extent of damage on bridge decks. The current bridge deck inspection method being employed by CDOT is sounding and chipping. This procedure involves sounding the deck with chains, hammers and rotary percussion to detect the deteriorated areas followed by chipping. The issues with this procedure include its time-consuming nature, the requirement for traffic to be diverted for extended periods and the costs associated with the inspection and traffic diversion. Additionally, sounding is not adequate to provide a rough estimation of the class of damaged area and the resulting expenses. CDOT wants to take the advantage of newer alternative techniques to evaluate bridge decks. The alternative evaluation considered by CDOT involves using Ground Penetrating Radar (GPR) and Infrared Thermography (IR) thermography together for evaluating bridge decks. The major advantage of using GPR is that it is the only available method that can estimate the deterioration in concrete decks with asphalt overlay. Additionally, GPR can estimate the deterioration in early stages, unlike sounding which detects damage in advanced stages and GPR is also capable of detecting corrosion in rebars. Thus, GPR not only has the potential to address the disadvantages of sounding it also has additional advantages which can benefit the life of the bridge deck. This study attempts to understand the limitations that this newer evaluation method comes with and possibly solve some of these limitations to take complete advantage of this technology. This study took advantage of the available as-built data of four bridge decks rebuilt after sounding and chipping and the data available from GPR and IR scanning of the respective decks to study the limitations from using GPR and IR technologies. The scanned results from GPR and IR thermography are compared to the deck condition data from sounding and chipping. In two cases the damage detected by GPR and IR thermography did not correlate well with the damage detected from sounding and chipping. The two decks with reasonable correlation are compared to the decks with poor correlation in an effort to understand the possible causes for deviation in results. It was observed that for the decks with poor correlation the GPR showed areas with higher cover as deteriorated in the estimation. An improved data processing procedure to solve such miss-interpretation issue is suggested, and a coring strategy to assist future research in the direction of eliminating the depth-amplitude effects in GPR scans.
Keywords: bridge deck evaluation; GPR; NDE; bridge deck inspection; bridge deck; IR